PENGARUH KEPEMIMPINAN DAN IKLIM KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL (PNS) PADA BADAN PERENCANAAN PENELITIAN DAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN MOROWALI - Suarni, Suarni (Katalogis, 2016)
The research objectives are: 1) to test and analyze the significant influence of leadership and work climate on civil servants’ performance in The Agency of Planning, Research, and Regional Development (Bappeda), Morowali Regency; 2) to test and analyze significant influence of leadership on civil servants’ performance; 3) to test and analyze significant influence of work climate on civil servants’ performance. This is a quantitative research that looking at the influence among variables by involving 39 respondents selected through census method. Multiple linear regressions test shows that: 1) leadership and work climate simultaneously have positive and significant influence on civil servants’ performance in The Agency of Planning, Research, and Regional Development, Morowaly Regency; 2) leadership has positive and significant influence on offcials’ performance; 3) work climate has positive and significant influence on civil servants’ performance.